2006
DOI: 10.1038/nature05163
|View full text |Cite
|
Sign up to set email alerts
|

Long-period astronomical forcing of mammal turnover

Abstract: Mammals are among the fastest-radiating groups, being charac terized by a mean species lifespan of the order of 2.5 million years Changes in organisms occur on a variety of temporal scales. Four basic temporal scales (tiers) have been recognized: the ecological timescale; the Milankovitch timescale of precession (the wobbling of the Earth's axis, �21 kyr periodicity), obliquity (tilt of the Earth's axis, 41 kyr periodicity) and eccentricity (the orbit around the Sun, � 100 and �400 kyr periodicity); the millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(131 citation statements)
references
References 24 publications
10
117
2
2
Order By: Relevance
“…We show that large-scale parameters of species' niches, in this case temperature and salinity, do not change for a phylogenetically and ecologically diverse set of marine molluscs. Although species may modify their behaviour or resource utilization, the FN places constraints on species' interactions with the environment, which potentially governs speciation and extinction processes over long time scales [10,89]. Some researchers have suggested that niche stability may promote allopatric speciation [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…We show that large-scale parameters of species' niches, in this case temperature and salinity, do not change for a phylogenetically and ecologically diverse set of marine molluscs. Although species may modify their behaviour or resource utilization, the FN places constraints on species' interactions with the environment, which potentially governs speciation and extinction processes over long time scales [10,89]. Some researchers have suggested that niche stability may promote allopatric speciation [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…The reptile-like physiological and life history traits found in Myotragus were certainly crucial to their survival on a small island for the amazing period of 5.2 million years, more than twice the average persistence of continental species (42). Therefore, we expect similar physiological and life history traits to be present in other large insular mammals such as dwarf elephants, hippos, and deer.…”
Section: Discussionmentioning
confidence: 84%
“…In recent works, the modulation of the 405 kyr component, which is caused by the beat g 3 −g 4 of period ≈2.4 Myr, has also been identified in the sedimentary records, and is thought to be a key factor in the onset of special climate events (Lourens et al 2005;Pälike et al 2006;van Dam et al 2006). There have also 3 The secular frequencies are the frequencies of the slow precessing motion of the orbit in its plane (precession of perihelion) and of the slow motion of the plane of the orbit in space (precession of the node).…”
Section: Long-term Cyclesmentioning
confidence: 99%